Generalized W-algebras and integrable hierarchies - Timothy Hollowood (Physics Letters B, 1991)
We report on generalizations of the KdV-type integrable hierarchies of Drinfel'd and Sokolov. These hierarchies lead to the existence of new classical $W$-algebras, which arise as the second Hamiltonian structure of the hierarchies. In particular, we present a construction of the $W_n~{(l)}$